Proposed strategies for lightning performance improvement of 35 kV distribution lines in Vietnam - Tung Tran, Anh; Son Tran, Thanh (Institute of Advanced Engineering and Science, 2025)
Lightning strikes frequently cause power outages on 35 kV distribution lines in Vietnam. These lines was normally protected with a sparse density of surge arrester and typically do not make use of shield wire. On the other hand, a single rod, that is frequently used as the grounding electrode, is not suitable for some region with high value of soil resistivity. Therefore, it is of particular of interest to investigate the solutions to protect the medium voltage lines from the back-flashover due to lightning strikes by analyzing the impact of the grounding impedance, the surge arrester density and the installation of the shield wire. The finite element method and the electromagnetic transient program EMTP-RV are combined in this work to propose techniques for increasing the critical flashover current of 35 kV lines in Hanoi city. The obtained results showed that the installation of shield wires combined with high density of surge arrester and reduced grounding impedance value can achive a very significant improvement of the overall lightning performance of the line.